Global Peace: Myth or Reality? - Pattila Puzhankara, Renuka Devi (INTI International University, 2009)
The call for peace is universal and timeless, since conflict is always with us. Its shadow is found in all cultures in all times, beckoning for response. When constructive it leads to better understanding and deeper relationships. When destructive, it tends towards confusion and separation. There is no iota of doubt that there cannot be a world without peace. The ultimate goal of a righteous war is peace. However, can this goal ever be achieved? Since wars continue without stopping, one cannot admit the possibility of an all time global peace. What is peace? Is it a myth or is it a reality? My main focus is to nurture awareness and enhance capabilities for the building of lasting peace and foster a holistic understanding of the interconnected impact of the family, school and society on our perspectives of peace by emphasizing on the following points. 1. The need for an understanding on urgent peace issues facing humanity 2. Reflections on the roots of violence, war, revolution and terrorism 3. Measures to quell violence and sustain peace for ever 4. How education can be transformed to bring true peace to the World?